Smoking and the Risk of Type 2 Diabetes: A Cross-sectional Analytical Study - Dhrubajyoti J. Debnath; Jayanti Ray; Syed Mustafa Jah; Yamini Marimuthu (Wolters Kluwer Medknow Publications, 2024)
Background: India is undergoing epidemiological transitions with the increase in noncommunicable disease (NCD) burden. Targeting the modifiable risk factors through lifestyle changes in the early years of life remains the most effective strategy for decreasing the prevalence of type 2 diabetes mellitus (T2DM). To determine the association between cigarette smoking and T2DM. Materials and Methods: An analytical cross-sectional study was conducted among the patients attending the outpatient department of a tertiary care teaching hospital in Kolkata, West Bengal, India. Patients aged more than 35 years were enrolled, and details regarding sociodemography, clinical status, and NCD risk factors were collected using pretested semistructured questionnaires after obtaining IEC approval. Data collected were entered in MS Excel and analyzed using SPSS software. Simple logistic regression and multivariable logistic regression analysis were used to calculate the crude and adjusted odds ratio with 95% confidence interval. Results: Out of 434 participants, 37.3% had diabetes mellitus, 51.6% were males, and 28.6% had alcohol consumption. Univariate logistic regression analysis revealed age, BMI, systolic BP, diastolic BP, and cigarette smoking were significantly associated with increased risk of T2DM. Multivariable logistic regression analysis revealed cigarette smoking, systolic BP, age, and female gender were significant risk factors for T2DM. Conclusions: Our study reported cigarette smoking and systolic BP are modifiable risk factors associated with T2DM. Early identification of smoking through screening and appropriate control of hypertension in T2DM patients will decrease the morbidities and mortalities in T2DM cases.